2020
DOI: 10.17784/mtprehabjournal.2020.18.811
|View full text |Cite
|
Sign up to set email alerts
|

Intra-examiner and inter-examiner reliability in the determination of angular measurements of the wrist using a smartphone application

Abstract: Purpose: With recent technological advances, goniometric applications have increasingly been used for the measurement of joint angles due to the greater practicality and accessibility. It is therefore important to determine the reliability of these applications. The evaluation of the wrist is important, as this joint is commonly affected by trauma that can lead to limitations of movement. Thus, the aim of the study was to determine the intra-examiner and inter-examiner reliability of the Goniometer PRO© smartp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recently, several smartphone applications have become available that provide an alternative method of monitoring joint angles [11]. Wassmuth et al found the Goniometer PRO to be an effective tool for evaluating wrist ROM [12]. Similar results were found in forearm supination using the DrGoniometer, which is a valid and alternative tool for measuring ROM [13].…”
Section: Introductionmentioning
confidence: 88%
“…Recently, several smartphone applications have become available that provide an alternative method of monitoring joint angles [11]. Wassmuth et al found the Goniometer PRO to be an effective tool for evaluating wrist ROM [12]. Similar results were found in forearm supination using the DrGoniometer, which is a valid and alternative tool for measuring ROM [13].…”
Section: Introductionmentioning
confidence: 88%
“…[ 16 ] Regarding intra-examiner reliability, each examiner examined a group of 25 subjects twice, with a time interval of at least 30 minutes between examinations; the intraclass correlation coefficient was >93%; which was considered excellent based on Fleiss. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%